PENGARUH UKURAN PERUSAHAAN, LEVERAGE, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN - Muhammad Rivandi; Berta Agus Petra (Jurnal Inovasi Penelitian, 2022)
ABSTRACT Maximize value of enterprise of crucial importance to a company, be an increase in the value of enterprise ineffective with satisfaction the shareholders as early as. The company was assessed as good when share prices high in the capital market. If the price of a stock company has high the riches of company owner will increase. This study aims to analyze due to the size of the company, leverage, and on the perceived value of the company profitability in the new company sub food and beverages sectors who are enrolled in BEI years 2016-2020. The sampling method used is the Purposive Sampling Method with a sample of 12 food and beverage sub sector companies listed on the BEI in 2016-2020. The data analysis technique is panel data regression. The results of the study prove that firm size has a negative and significant effect on firm value, leverage has no effect on firm value, and profitability has a positive and significant effect on firm value. Keywords: the size of the company, leverage, profitability, and the value of the company.